The Effect of Using Modern English Song Lyrics to The Vocabulary Mastery of Grade VIII - Subandi Maulana, Erik; Putraidi, Karyawan; Hamjah, Hamjah (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study investigates the effectiveness of modern English song lyrics as a medium for improving vocabulary mastery among eighth-grade students at SMPN 3 Praya in the academic year 2025/2026. A quantitative approach with a quasi-experimental design was employed, involving two groups: the experimental class taught using modern English songs and the control class taught with conventional methods. Each class consisted of 24 students selected purposively. Data were collected through pre-tests, post-tests, questionnaires, and documentation, and analyzed using descriptive statistics, normality and homogeneity tests, paired sample t-tests, and Mann-Whitney U tests. Findings revealed that the experimental group’s mean score increased significantly from 34.79 to 72.08, while the control group improved from 40.58 to 60.83. Statistical results confirmed that the difference between the groups was significant (p < 0.05). These outcomes suggest that modern English song lyrics not only enhance vocabulary mastery but also foster student motivation and classroom engagement. The study concludes that incorporating modern English songs into English teaching can create a more dynamic and enjoyable learning environment.